Microstructure and mechanical properties of AA 2219-TiB2 composites by squeeze casting technique. (2020) - Karthik, A.; Karunanithi, R.; Srinivasan, S.A.; Prashanth, M.
Abstract: The AA2219 alloy has been investigated by using squeeze casting process and the reinforcement of TiB2 is added to improve mechanical property and grain morphology to match the requirement of aerospace and automotive industries. The AA2219 alloy and composites sample were prepared by squeeze casting process and process parameter were kept at 350 MPa squeeze pressure load, die and melt temperature as 200°C and 650°C respectively with the standard dwell time 60 s. The weight percentage (x = 0, 2.5, 5 and 7.5) reinforcement of TiB2 added with AA2219 alloy. The morphology and phase of prepared samples are evaluated by using light microscopy, X-ray diffraction, scanning electron microscopic and energy dispersive technique. The reinforcement of TiB2 resulted in grain refinement of alloy attaining equiaxial and homogeneous grain structure. Mechanical properties such as micro hardness and tensile strength have been enhanced by 22% and 89% respectively. Wear analysis performed on the composite with help of pin on disk setup and wear characteristic show excellent wear resistance.